Indonesia Master of Education Student’s Perceptions of Their Experience in Learning Tesol in the Tertiary Context in Australia - Neni Djafar (Universitas Pendidikan Muhammadiyah Sorong, 2019)
The aim of research study is to investigate the manner how experience in learning TESOL in tertiary context in Australia impacts on Indonesian M.Ed Students’ perception in the English language learning and in the English language teaching in their context. Although there have been many studies conducted with regard to the perceptions of international students with non-English backgrounds from Asian countries, there is no specific study yet conducted pertaining to how experience in learning TESOL in tertiary context in Australia impacts on Indonesian M.Ed Students’ perception in the English language learning and in the English language teaching in their context. The method used to collect data from the participants of the study consisting of eight of them is an individual semi-structured interview with openended questions and descriptive thematic analysis to analyze the data to generate the result of the study.